(untitled) - Sullivan, Michael (Chicago, IL, 2005)
This book is intended to be a guide for the new or future children's librarian. the book covers the gamut of topics that you would expect to find in such a text including collection development ; services ; programming ; and management, administration, and leadership. Author also discusses the role of children's services and the principles of children's librarianship. Topics are not covered in great depth but the content does touch on the essential elements. Insets within the chapters discuss issues such as librarian shortages and pay equity, service to boys, children and privacy, and library programs and copyright. Other insets give suggested titles for storyhours, a sample press release, and Web resources
Keywords: Children’s libraries,Thư viện trẻ em; United States,Hoa Kỳ